Answer :

junkyarddogg

Answer:

x = 13/3 or 4.3 repeating (4.333333.....)

Explanation:

3x + 2(4x - 6) = 8x + 1

3x + 8x - 12 = 8x + 1 (expand using distributive property)

11x - 12 = 8x + 1 (combine like terms)

11x - 12 + 12 = 8x + 1 + 12 (add 12 to both sides)

11x = 8x + 13 (simplify)

11x - 8x = 8x - 8x + 13 (subtract 8x from both sides)

3x = 13 (simplify)

3x/3 = 13/3 (divide both sides by 3)

x = 13/3 or 4.3 repeating (4.333333.....)

1234alex101

Answer:

3x + 2(4x − 6) = 8x + 1 the value of x would be...

x= 13/3

Explanation:

Hope this helps :)

Other Questions